A new route to fast accurate design tool for open planar circuit analysis - Balik, Hasan H.; Railton, C.J. (My University, 2002)
Spectral Domain Method (SDM) is one of the best known techniques for developing full-wave design tool at the operating frequency of interest. However full-wave analysis requires more computer power and takes time to yield results. The aim of this paper is to enhance SDM to make it as fast as the simpler methods. The SDM analysis requires the definition of the unknown current distribution on the metallisation of the circuit. The minimisation of the number of basis functions required is crucial to the efficiency of the technique, therefore, sub-gridding, the inclusion of a priori knowledge of current distribution by using precalculated current basis functions and re-mapping of precalculated basis function are employed in the present implementation.
Novi pristup brzom i to?nom projektiranju u analizi otvorenog ravninskog strujnog kruga
Keywords: Current basis functions; Planar circuits; Precalculated current basis function; Priori-knowledge; Re-mapping; Spectral domain method; Sub-gridding